Circularly Polarized Dual-Band LoRa/GPS Antenna for a UAV-Assisted Hazardous Gas and Aerosol Sensor - Mira, Fermín (Micromachines (Basel), 2021)
UAV assisted wireless sensor networks play a key role in the detection of toxic gases and aerosols. UAVs can be used to remotely deploy sensor nodes and then collect gas concentration readings and GPS positioning from them to delimit an affected area. For such purpose, a dual-band communication system is required, supporting GPS reception, and sensor reading data transfer, which is chosen to be at 2.4 GHz using LoRa physical layer. In this work we propose a switched-beam antenna subsystem for the sensor nodes capable not only of satisfying the dual band requirements but also of maximizing communication range or energy consumption through a good antenna polarization match and improved antenna gain. This antenna subsystem is built using dual-port, dual-band, circularly polarized antenna elements, whose design and experimental validation is carefully detailed. A low profile microstrip stacked structure has been used to obtain return loss in both bands better than 15 dB, axial ratios below 1.5 dB, and wide −3 dB beamwidths around 90° and 75° for GPS and 2.4 GHz bands, respectively, thus limiting the gain reduction of the switched-beam system in critical sensor orientations. Special attention has been paid to reduce the coupling between both ports through the optimization of the relative placement of both patches and their feeding points. The measured coupling is below −30 dB.